Seven minus negative two times negative 4 is equal to -1
Simple math rules state that a negative times a negative equals a positive!
Three times negative 2 minus three is equal to -9
you get a negative
You cannot solve it though it is possible to evaluate the expression. -5 + 9 * 6 = -5 + 54 = 49
To write the expression "negative ten times the quantity two minus eleven" in numbers, you would first simplify the expression within the parentheses. Two minus eleven equals negative nine. Then, you multiply negative ten by negative nine to get positive ninety. Therefore, the expression "negative ten times the quantity two minus eleven" can be written as -10 * (2 - 11) = 90.
Positive (Plus) times Negative (Minus) always equals a negative (minus).
It could be: -3/8+4x-9z as an algebraic expression
The quotient of a positive integer by a negative is always negative. Say this to yourself a couple times: "MULTIPLICATION: minus times minus is plus (negative x negative = positive).....minus times plus is minus (negative x positive = negative).....plus times plus is plus (positive x positive = positive) DIVISION: minus divi minus is plus (negative ÷ negative = positive)......minus divi plus is minus (negative ÷ positive = negative).....plus divi plus is plus (positive ÷ positive = positive)"
Seven minus negative two times negative 4 is equal to -1
Simple math rules state that a negative times a negative equals a positive!
Negative times positive equals negative.
I honestly don't know :D but heres something to help you "MULTIPLICATION: minus times minus is plus (negative x negative = positive).....minus times plus is minus (negative x positive = negative).....plus times plus is plus (positive x positive = positive) DIVISION: minus divi minus is plus (negative ÷ negative = positive)......minus divi plus is minus (negative ÷ positive = negative).....plus divi plus is plus (positive ÷ positive = positive)"
Three times negative 2 minus three is equal to -9
negative 49. This is because a minus multiplied by a plus is a minus.
you get a negative
You cannot solve it though it is possible to evaluate the expression. -5 + 9 * 6 = -5 + 54 = 49